The Idea of Change in Simone Weil’s Early Philosophy - Ruiz Jiménez, Juan Manuel (2025)
“The Idea of Change in Simone Weil’s Early Philosophy”. Given that Simone Weil’s oeuvre is characterized by profound reflections on time, which she consistently regarded as the ontological and cognitive instance through which the feeling of human reality acquires meaning, this paper seeks to elucidate the concept of change, which plays a central role in her early philosophy and, in my view, sheds light on the temporal categories of her later work. To achieve this, I examine the dual epistemological condition of human perception posited by Weil in several key texts from her early period –namely, the change present in all phenomena perceived in time and space, and the immobility of the object of thought–. Additionally, I explore the implications of this concept for human understanding of the world.